Hyperinsulinemia and hyperglycemia: risk factors for recurrence of benign paroxysmal positional vertigo - Webster,Guilherme (2015)
INTRODUCTION: Changes in carbohydrate metabolism may lead to recurrence of benign paroxysmal positional vertigo.OBJECTIVE: To evaluate the influence of the disturbance of carbohydrate metabolism in the recurrence of idiopathic BPPV.METHODS: A longitudinal prospective study of a cohort, with 41 months follow-up. We analyzed the results of 72 glucose-insulin curves in patients with recurrence of BPPV. The curves were classified into intolerance, hyperinsulinemia, hyperglycemia and normal.RESULTS: The RR for hyperinsulinism was 4.66 and p = 0.0015. Existing hyperglycemia showed an RR = 2.47, with p = 0.0123. Glucose intolerance had a RR of 0.63, with p = 0.096. When the examination was within normal limits, the result was RR = 0.2225 and p = 0.030.DISCUSSION: Metabolic changes can cause dizziness and vertigo and are very common in people who have cochleovestibular disorders. However, few studies discuss the relationship between idiopathic BPPV and alterations in carbohydrate metabolism. In the present study, we found that both hyperglycemia and hyperinsulinemia are risk factors for the recurrence of BPPV, whereas a normal test was considered a protective factor; all these were statistically significant. Glucose intolerance that was already present was not statistically significant in the group evaluated.CONCLUSION: Hyperinsulinemia and hyperglycemia are risk factors for the recurrence of idiopathic BPPV and a normal exam is considered a protective factor.